A study of attitude towards the use of ICT amongst working women / Faridah Abd. Rahman - Abd. Rahman, Faridah (2014)
The purpose of this study was to investigate the attitude of working women towards the use of Information and Communication Technology (ICT) at workplace. Seven constructs includes demographic characteristics have been determined in a research model which formulated based on Technology Acceptance Model (TAM) and extended TAM. A set of questionnaire was formulated based on the research model and has been used in data collection through online and paper based survey. 81 female employees from government and private sectors participated in this study. However, only 78 usable responses were analyzed and used in this study. Descriptive statistics, a one-way ANOVA, and correlation analysis were conducted to analyze the data from the survey regarding to the study of attitude of working women towards the use of ICT. The major of finding this study revealed that majority of working women in Klang Valley possess negative attitudes regarding to the use of ICT. Pearson Product-Moment Correlation Coefficient was used to conduct hypotheses testing in order to investigate the relationship between perceived usefulness and attitudes of respondents towards the use of ICT. The result revealed that perceived usefulness has significant correlation on attitudes of working women toward ICT. Apart of that, the study also revealed there was a strong correlation between perceived ease of use and attitudes toward ICT among working women. Furthermore, a one-way ANOVA was used to conduct a hypotheses testing to identify whether demographic characteristics influence the attitudes of female employees toward ICT. The results indicated that the female employees from different group of academic qualification have different attitude towards the use of ICT. Further investigation was conducted by using Least Significant Difference (LSD) Post Hoc Multiple Comparison test to identify which group of academic qualification in demographic characteristics scores higher or lower in their attitudes toward ICT. Based on the findings, it can be concluded that female employees with Diploma have positive attitudes toward the use of ICT as compared to the female employees with Masters or PhD holder. Moreover, this study had discussed the significance of the findings. Finally, this study includes several recommendations which useful to provide wider perspective to subsequent research.